Data Classification of Marriage Readiness in Young Adults Using the Naïve Bayes Algorithm - Rahmi Fauziah; Heru Satria Tambunan; Susiani Susiani (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
Readiness to get married usually must be owned by every individual who wants to run a married life in order to become a harmonious family. However, not all young adults prepare for marriage such as financially, emotionally, roles and others. So the classification is carried out to determine the readiness for marriage with ready and not ready classes. Classification is part of data mining that performs the process of building a model based on existing training data, then using the model for classification on new data. The research data used were taken from 103 young adult, male and female. The algorithm used is Naïve Bayes. The conclusion of this research is testing as much as 5 testing data that is processed in RapidMiner 5.3. get test results with an accuracy of 74,33%, namely 3 data that are not ready and 2 data that are ready. So that the research process can be done quickly and efficiently.